Mapeamento temático da cibercultura no campo da ciência da informação: uma visão crítica - Oliveira, Fabio Moreira de (2013)
This Master thesis aims providing a thematic mapping of part of the knowledge produced in scientific literature in the field of information science related to the cyberculture. The articles on cyberculture published in the scientific journals Information Science and Perspectives in Information Science are the object of this research study. The specific objectives try to present and contextualize cyberculture, understood here, as social organizations originated from technological advances after the outbreak of World War II, and discuss from the selected content, the main theme of the inflections. The sampling gathered 57 serial numbers covered the period 2001 to 2010. We selected 181 scientific articles that address the topic in question. The strategy adopted in addition to research and review literature, was the thematic analysis. The theoretical perspectives that have echoed in the context of the research were the postmodern (Lyotard, Harvey, Jameson and Kumar), the utopia of communication (Breton), critical theory of communication post-Frankfurt School (Sfez), the sociodromology (Virilio), the epistemology of critical cyberculture (Trivinho), among other aspects of proximity and theoretical coherence. Finally, the results of studies led to the conclusion that the myth of digital inclusion and democratization of access revolves around the theme of cyberculture in the field of Information Science